Programa de intervención psicoeducativo para potenciar la autoestima en los estudiantes del octavo año de educación básica paralelo “C”, de la unidad educativa anexa a la Universidad Nacional de Loja, 2013-2014 - Robles Hurtado, Yesenia Corcina (2015)
The Research: Intervention Psychoeducational Program to enhance self-esteem in students of the eighth year of Basic Education. It was aimed to implement an intervention Psychoeducational Program to increase self-esteem. It was a descriptive transversal study with a quasi-experimental design, 33 students were taken as a sample. It was supported by methods: scientific, inductive-deductive, analytic, synthetic, understanding, diagnosis, development and implementation of the model, besides that the survey and the Reild's self-esteem Scale were used. Results: at 69.70% has trouble in accepting themselves as they are, 78.79% the low self-esteem cause suffering. The pre-test report that 66.67% have low self-esteem, after the Psychoeducative intervention the post-test shows that the 12.12% have low self-esteem; to evaluate the program effectivity, the r(x,y)=0.90 means that it is valid and relevant. Conclusions: The low self-esteem in students from eighth grade "C" interferes with interpersonal relationships.